Rattus hainaldi Kitchener, How, and Maharadatunkamsi 1991 - Wilson, Don E.; Reeder, DeeAnn (The Johns Hopkins University Press, 2005)
Rattus hainaldi Kitchener, How, and Maharadatunkamsi 1991 Rattus hainaldi Kitchener, How, and Maharadatunkamsi 1991, Rec. West. Aust. Mus., 15: 557. Type Locality: Indonesia, Nusa Tenggara, Pulau Flores, Gunung Ranakah, 1300 m, above Kampong Robo, Desa Longko, 8 km SSE Ruteng. Vernacular Names: Hainald's Flores Island Rat. Distribution: Known only from Flores Isl. Conservation: IUCN – Lower Risk (nt). Discussion: Rattus species group unresolved. Described from two specimens (Kitchener et al., 1991 c ), and later found to be common in forest habitats (Kitchener and Yani, 1998; Kitchener et al., 1998). Phylogenetic affinities uncertain; placement in Rattus originally provisional (Kitchener et al., 1991), results from albumin immunology suggest transfer to either Bunomys or Komodomys (Watts and Baverstock, 1994 b ), but electrophoretic data indicate R. hainaldi to be equidistant from the Komodomys-Rattus timorensis clade of Nusa Tenggara clade and true Rattus (K. Aplin, in litt., 2004). Published as part of Wilson, Don E. & Reeder, DeeAnn, 2005, Order Rodentia - Family Muridae, pp. 1189-1531 in Mammal Species of the World: a Taxonomic and Geographic Reference (3 rd Edition), Volume 2, Baltimore :The Johns Hopkins University Press on page 1471, DOI: 10.5281/zenodo.7316535